Еcologically ensuring imperatives of innovative development of construction enterprises - ZINCHENKO, Myroslava; NAZVANOV, Denys (Ways to Improve Construction Efficiency, 2025)
This article delves into the eco-security imperatives as fundamental strategic components of innovative development amid intensifying global environmental challenges and the ongoing transformation of economic and technological systems. It emphasizes that sustainable innovation should be grounded not only in the pursuit of technological advancement but also in the systemic integration of ecological priorities aimed at preserving natural ecosystems, ensuring environmental safety, and reducing the anthropogenic burden on the environment. The research outlines the theoretical and methodological foundations of eco-oriented innovation policy, advocating for the transition to sustainable development models such as the green economy, circular production systems, eco-efficiency, and environmentally responsible design practices. The paper underscores the necessity of a holistic and interdisciplinary approach to innovation, in which environmental concerns are not secondary but rather embedded in the core logic of economic and technological progress. In this context, particular attention is paid to the role of state environmental policy, ecological responsibility of businesses, institutional mechanisms for ecological governance, public-private partnerships, and the formation of ecological consciousness and culture within society. Barriers to the integration of environmental imperatives into innovation strategies are identified, including the fragmentation of environmental legislation, insufficient investment in green technologies, low levels of environmental education and awareness, and the lack of incentives for environmentally sound practices. The article also presents promising directions for fostering eco-innovations, such as the creation of green innovation clusters, investment in sustainable infrastructure, implementation of environmental management systems, and strengthening the role of environmental criteria in technological evaluation and policy planning. The study concludes that eco-security imperatives must become an essential part of national and global innovation strategies. They should not be treated as regulatory constraints but rather as catalysts for a new wave of sustainable technological progress that ensures a balanced interaction between the economy, society, and the natural environment.